2019
DOI: 10.1002/lary.28096
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative uvular necrosis: A case series and literature review

Abstract: Objectives/Hypothesis Postoperative uvular necrosis is rare, but can be distressing to the patient when it unexpectedly occurs. Little has been published regarding its predisposing factors and pathophysiology. The purpose of this comprehensive review was to compile cases of postoperative uvular necrosis and identify risk factors and potential causes for this complication. Study Design Retrospective case series. Methods The study was performed at an academic tertiary care referral center. Clinical records from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(36 citation statements)
references
References 29 publications
0
36
0
Order By: Relevance
“…3,4 Men represented three-quarters of all reported cases but there were no other associations reported with the type or length of procedure, or the type or size of oropharyngeal airway. 3 The largest study included ten patients, and reported an incidence of 0.034% over four years at a single tertiary centre. 5 It is unclear whether there are any specific preventable factors, or any specific management strategies that might reduce this complication.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…3,4 Men represented three-quarters of all reported cases but there were no other associations reported with the type or length of procedure, or the type or size of oropharyngeal airway. 3 The largest study included ten patients, and reported an incidence of 0.034% over four years at a single tertiary centre. 5 It is unclear whether there are any specific preventable factors, or any specific management strategies that might reduce this complication.…”
Section: Introductionmentioning
confidence: 92%
“…endotracheal tubes (ETTs), laryngeal masks, upper gastrointestinal endoscopy, transoesophageal echocardiogram, aggressive oropharyngeal suction). 2,3 A brief literature search (including PubMed, CINAHL Complete, Embase) found a total of 53 reported cases of uvular necrosis worldwide, with the first report published in 1978. 3,4 Men represented three-quarters of all reported cases but there were no other associations reported with the type or length of procedure, or the type or size of oropharyngeal airway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Uvular necrosis is most commonly iatrogenic, following intubation, endoscopy or suction. 5 Most documented cases, predominantly in adults, resolve conservatively, with necrotic tissue sloughing off in 7-14 days. 5 Contributors Patient seen by all three authors.…”
Section: Images In…mentioning
confidence: 99%
“…5 Most documented cases, predominantly in adults, resolve conservatively, with necrotic tissue sloughing off in 7-14 days. 5 Contributors Patient seen by all three authors. JP took photographs.…”
Section: Images In…mentioning
confidence: 99%